Level of Existential Future Anxiety Among A sample of Palestinian Students Who Hold Refugee Status in Palestine - Akwanin, Faris Mahmoud (Journal of Educational and Psychological Sciences, 2022)
The study aimed to reveal the level of existential future anxiety among a sample of Palestinian students who hold refugee status, as well as reveal the existence of statistically significant differences depending on research variables (gender, type of study). the researcher used the descriptive analytical method, the sample consisted of (400) male and female students who hold refugee status in the West Bank. The study used the existential future anxiety scale prepared by the researcher. The results concluded in the following that the level of existential anxiety among Palestinian refugee students is medium. There are statistically significant differences at the level of significance (0.05≥α) in the level of existential future anxiety among a sample of Palestinian students who hold refugee status. This is according to the gender variable and in favor of males, there are no differences in the level of existential future anxiety in the sample of Palestinian students who hold refugee status، depending on the variable of the type of study.